Effect of Nursing Intervention regarding Centers for Disease Control and Prevention Guidelines on Nursing Knowledge in Operating Room : Nursing Intervention regarding Disease Control and Prevention - Tabassum, Zahida; Masih, Sarfraz; Afzal, Muhammad; Khan, Sadia (Pakistan Journal of Health Sciences, 2023)
Sterilization techniques are the basic and important responsibility of health care professional’s especially nurses. Objective: To evaluate effect of intervention CDC guidelines on nurses’ knowledge regarding Aseptic techniques in operating room. Methods: A quasi experimental study was conducted on 46 male and female nurses working in the operating room and having experience in operating room more than six months. A random sampling technique was used for data collection. The questionnaire consists of 22 questions about the knowledge of nurses regarding sterile techniques. Nurses were given 3-month intervention regarding aseptic technique, pre and post data was gathered from nurses regarding sterile techniques in operating rooms. Data were entered and analyzed in SPSS version 24. For quantitative variables mean and SD was computed. For categorical variables frequency and percentages was computed. p-value < 0.05 was considered statistically significant. Results: The majority of nurses were married and female and 32 (69.6%) were between the age group 25-35 years. In the post-intervention phase there were 0(0), 21(45.7%) and 25(54.3%) participants had poor, fair and good knowledge respectively regarding aseptic techniques in operating room. The findings revealed that there was a significant difference between pre and post interventional practice scores as evident by (p-value <0.001). Conclusion: The current study concluded that the educational interventions on operation room nurses significantly enhance operating room nurses’ knowledge regarding aseptic techniques